ANALYSIS OF FINANCIAL PERFORMANCE AND SHARE PERFORMANCE BEFORE AND AFTER THE COVID-19 PANDEMIC ON THE IDX - Widyawati, Nur Laili; Ningtyas, Mega Noerman (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
The goal of this research was to examine if there were any differences in financial performance and share performance of companies listed on the Indonesia Stock Exchange (IDX) before and after the Covid-19 pandemics was announced. Listed companies on the Indonesia Stock Exchange at least in 2018 make up the research population. There were 487 companies in this study's sample. The research data was collected through purposive sampling. The study's findings show that the liquidity ratios, profitability ratios, solvency ratios, activity ratios, market ratios, and abnormal returns have substantial differences. The beta (stock risk) variable, on the other hand, shows no significant differences. Between before and after the Covid-19 pandemic was announced, the liquidity ratio (current ratio), profitability ratios (return on assets), activity ratio (asset turnover), and market ratio (price-earnings ratio) all decreased. In the meantime, the solvency ratio (debt to equity), abnormal returns, and stock beta have all risen.